Culturas do corpo e da juventude nas redes sociais digitais: uma cartografia dos imaginários midiáticos e do culto de celebridades no Instagram - Aprobato, Valéria Cristiane (2018)
What are the discourses on digital social networks that circulate around the themes of the search for the perfect body and eternal youth? In the context of the numerous publications on beauty, health and good shape present in cyberspace (Leão), this thesis is based on the hypothesis that there is a complex social imaginary being built in the networks and that it is possible to map the affections, practices and the logics that compose this imaginary. The research method involved: theoretical research (reading of texts and bibliographical review of the literature); empirical research composed by: (1) analysis of speeches present in celebrity networks; (2) questionnaires and interviews with followers of selected social networks; (3) cartography. The chosen corpus consists of "Instagram" pages by Jane Fonda, Arnold Schwarzenegger, Bela Gil, Bella Falconi and Kéfera. The theoretical foundation is composed by Foucault (discourses of power, biopolitics and subjectivity); Leão (network culture, mitoanalysis and cartography as a method for researching media imagery); Spinoza (affections); Flusser and Proser (cultural studies on the notions of gluttony and vanity). As results achieved, we could verify that the desire’s discourses for perfect body and eternal youth shelter three mythical matrices of collective construction of subjectivities (heroic, transgressive and transformative). Thus, we understand that the present thesis is a contribution to the studies of the media imaginaries that populate the networks’ discourses about perfect body and eternal youth and that the use of the discourse mapping method was productive for the construction of an understanding of these complex subjectivities